(3eSGFd CHj MGRes - (3eMeO Hf eMeO GdbGVj GdaQGA GdMfHdj, CHj jYdj,J (B526 (3g` s
(3ChdgG (B:s
(3hcfJ MGLkG Edi HjJ Gddg GdMQGe hRjGQI bHQ GdfHi Ydjg CaVd GdUdGI hGdSdGe aHjfeG CfG SGFQ Ydi SGMd GdHMQ s
(3BNQgG (B:s
(3hCeG GdSfI GdJi eYgG KdGKI aQGFV agi GdfcGM aQGFV KdGKI Gdhdi hGdUOGb hGdTGgOGf hGddg SHMGfg hJYGdi CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HBNQgG aGFOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B23s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1667s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs